1988
DOI: 10.1007/bf00262730
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antitumor effects of the norepinephrine analogue meta-iodo-benzylguanidine (MIBG)

Abstract: Purpose Therapeutic options for patients with malignant pheochromocytoma are currently limited, and therefore new treatment approaches are being sought. Targeted radionuclide therapy provides tumor-specific systemic treatments. The β-emitting radio-pharmaceutical meta-131 I-iodo-benzylguanidine (131 I-MIBG) provides limited survival benefits and has adverse effects. A new generation of radionuclides for therapy using α-particles including meta-211 At-astato-benzylguanidine (211 At-MABG) are expected to have st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 7 publications
4
26
0
Order By: Relevance
“…In contrast, repeated oral administration of MIBG up to accumulated doses of 200 mg kg -1 did not induce histological damage of the kidney or other tissues. The absence of cumulative effects agrees with a previous study demonstrating absence of acute toxicity after repeated treatment at the maximum tolerated dose (Smets et al, 1988), and may be attributed to rapid clearance of the drug ( Figure 1B). Hyperaemia of the spleen is probably due to vascular effects as a result of MIBG-induced bioamine release (Kuin et al, 1994) or vasodilatation by inhibition of NOS (Kuin et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, repeated oral administration of MIBG up to accumulated doses of 200 mg kg -1 did not induce histological damage of the kidney or other tissues. The absence of cumulative effects agrees with a previous study demonstrating absence of acute toxicity after repeated treatment at the maximum tolerated dose (Smets et al, 1988), and may be attributed to rapid clearance of the drug ( Figure 1B). Hyperaemia of the spleen is probably due to vascular effects as a result of MIBG-induced bioamine release (Kuin et al, 1994) or vasodilatation by inhibition of NOS (Kuin et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…After i.p. administration, MIBG appeared to be lethal at single doses of just over 40 mg kg -1 MIBG, but not at 40 mg kg -1 for 9 sequential days (Smets et al, 1988). Side-effects encountered above 30 mg kg -1 i.p.…”
mentioning
confidence: 90%
“…MIBG is a known inhibitor of mitochondrial respiration (Smets et al, 1988;Biaglow et al, 1998;Loesberg et al, 1990) and a hyperglycaemia-induced shift to glycolysis has been shown to alter cellular oxygen consumption (Nadal-Desbarats et al, 2002). Therefore, we examined whether the glucose þ MIBG treatment could result in an increase in tumour pO 2 as reported by others (Burd et al, 2001(Burd et al, , 2003.…”
Section: Effects Of Tumour Acidification On Pomentioning
confidence: 87%
“…Previous studies have reported that MIBG can reduce oxygen consumption by tumour cells (Smets et al, 1988;Loesberg et al, 1990;Biaglow et al, 1998;), therefore we examined whether our tumour-acidifying protocol had secondary effects on tumour oxygenation. The KHT-C fibrosarcoma used in this study has previously been shown to be hypoxic with HP 5 values (tumour pO 2 values o5 mmHg) ranging from 25 -100% in individual tumours (median 68%); similar values have been reported in clinical soft tissue sarcomas with HP 5 values ranging from 0 -76% (Brizel et al, 1994;Nordsmark et al, 1996;De Jaeger et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, their taxol resistance is not due to their incapacity to be induced to death, either by apoptosis or necrosis; indeed, U937 cells underwent necrosis as well as apoptosis with a wide range of drugs, some of which, like PMC, induced apoptosis in almost all cells (Ghibelli et al, 1994;Dini et al, 1996;Bonanno et al, 2002). Moreover, another anticancer drug, MIBG, but with a mechanism different from that of taxol (Smets et al, 1988;Loesberg et al, 1990), was unable to induce cell death, thus confirming the intrinsic anticancer drug resistance of U937 cells. Shape modifications (i.e., large cytoplasmatic protrusions, many depolymerized microtubules), observed after incubation of U937 cells with taxol were not surprising.…”
Section: Discussionmentioning
confidence: 99%